Some Results and Analysis of Nonlocal Special Random Impulsive Fractional Differential Equations - Jose, Sayooj Aby; Tom, Ashitha; Valdes, Juan Eduardo Napoles; Sudsutad, Weerawat (Discontinuity, Nonlinearity, and Complexity, 2026)
The aim of the paper is to present an analysis of special random impulsive fractional differential equations involving Fredholm and Volterra integrals. This paper is mainly focused to the existence, uniqueness and stability of special random impulsive fractional differential equations with local initial conditions and nonlocal initial conditions separately. Such an approach enabled the generalisation of equations with local initial conditions and also helps in obtaining more practical results. To test the effectiveness of our results, we provide examples.